Argument and Authority in Early Modern England : The Presupposition of Oaths and Offices - Condren, Conal (Cambridge University Press, 2013)
The Language of Politics concentrated on the semantic residue from seventeenth-century England, and how it has been susceptible to rough treatment by modern scholars who, taking their own conceptual vocabulary for granted, have read it into the past. In particular, the terms radical, moderate, conservative, and their near relations left, right, centre, have been used with a redescriptive insouciance that has anachronistically distorted early-modern debate.8 For all the breadth of brush-stroke, it was argued that my case was incomplete because of inadequate attention to the conjectured principles, ideas and concepts to which I occasionally alluded.9 The point was well made, and this study is an attempt to rectify the imbalance. The purpose is to hypothesise a presupposition of office as an explanans for the sort of word use I have previously described and much more besides. It may or may not play a part in explaining state formation, but a thorough exploration of the linguistic terrain of office would seem to be a precondition for the success of that adjacent enterprise, just as it is for tracing specific theories of office as responses to a changing world. Indeed, if office-talk was as ubiquitous as I claim it was, the whole notion of early-modern political theory needs to be reconsidered